Local Wisdom and Community Participation in the Management of Wonosadi Customary Forest for Deforestation Prevention in Beji Village, Gunungkidul Regency, D.I.Y - Samani, Sarareza Pelita Dewa; Janitra, Lakeisha Yufa; Jovanca, Aurellius Widi Adam; Shara, Aprilia Riszi Indah Dewi (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2025)
Massive deforestation in Gunungkidul Regency, D.I.Y. Province’s largest forested area, has critically endangered local forest and water sources, causing forests and springs to almost become empty land. Customary forest management with community participation and local wisdom is one of the solutions to overcome the problem of deforestation in Wonosadi Customary Forest, Gunungkidul. The objectives of this study are: (1) to identify the concept of local wisdom in efforts to preserve Wonosadi Customary Forest in Beji Village, Gunungkidul, and (2) to analyze society participation in the management and prevention of deforestation of Wonosadi Customary Forest in Beji Village, Gunungkidul. The method in this research is descriptive qualitative. Data were collected through observation, interviews, documentation, and literature study. The results of the research show: (1) The form of local wisdom in Wonosadi Customary Forest is the belief in unwritten customary law, which is the basis of people's beliefs to prevent them from destroying the forest. (2) Community participation in efforts to manage and prevent deforestation in the Wonosadi Customary Forest is the formation of a Jagawana group named Ngudi Lestari as a forest management organization in the village.